Organisational, Renowned, and Charismatic Leaders: Three Types of Resources - Santilli, Cecilia; Scaramuzzino, Roberto (PARTECIPAZIONE E CONFLITTO, 2024)
Emerging research on civil society elites has highlighted the presence of elitist tendencies in European civil societies with a growing concentration of political and economic resources in the hands of small groups of major organizations and leaders. Building upon this strand of research, this article aims at studying the power stratification of Italian civil society-third sector through a systematic analysis of the distribution of three specific types of resources, namely organisational resources, reputation, and public visibility. For this purpose, we combine three methodological approaches. The study firstly draws on a large-scale mapping of civil society organizations and leaders at national level and follows the so-called "positional method". The second approach that we adopt in this study is the reputational analysis, based on a national survey conducted in 2021 which targeted 680 civil society leaders of organisations based on the same mapping of the positional approach. The third approach is the claims-making analysis, which consists in retrieving CS actors’ interventions on a given issue in the public domain drawing from media sources. Through the combination of these three methodological approaches, the study highlights the stratification of Italian civil society and the multi- dimensionality of power and influence among Italian Civil society elites. It also shows how the distribution of power resources lays on three main types of leaders-elites: the organizational leader, the renowned leader and the charismatic leader.